ASPEK PSIKOLOGIS PENGARANG DAN PENGARUHNYA TERHADAP PERWATAKAN TOKOH UTAMA NOVEL LADY CHATTERLAY’S LOVER KARYA DAVID HERBERT LAWRENCE - Imam Basuki (Faculty of Humanities, Jember University, 2015)
This article discusses a novel Lady Chatterlay’s Lover by David Herbert Lawrence. The story is based on the writer’s life background as well as the background of English economic, social and cultural condition before and after the first world war. The life experiences of Connie and her husband, Clifford, are taken as the main topic of this research by using expressive and psychological approaches. It is described that at the beginning Connie has a good personality but this chnges to be a bad one after her husband, Clifford, has got paralyzed. Such a condition has shifted her to be a woman who has no good character. She plunges herself into humiliating life by committing adultery with some other men. She has done it because she has never got what she hopes from his husband ; in addition, the economic condition of her family also gets decline as the impact of English economic, social and cultural condition before and after the first world war. The result of this research proves that the two backgrounds above have provided great psychological effects on the writer in doing characterization of the main character in this novel.Keywords: writer’s psychological aspect, characterization, the first world war